2021
DOI: 10.2196/26715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Online Obsessive-Compulsive Disorder Support Community Members: Survey Study

Abstract: Background People with obsessive-compulsive disorder (OCD) have faced unique challenges during the COVID-19 pandemic. Research from the first two months of the pandemic suggests that a small proportion of people with OCD experienced worsening in their OCD symptoms since the pandemic began, whereas the rest experienced either no change or an improvement in their symptoms. However, as society-level factors relating to the pandemic have evolved, the effects of the pandemic on people with OCD have like… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“… ( Benatti et al, 2020 ) Italy 123 patients with OCD Outpatient clinical sample, recruited from 3 tertiary clinics Age range not stated Not stated Not stated 35.8 % of patients reported worsening of symptoms during the pandemic, which was associated with developed of new obsessions and compulsions ( Chakraborty and Karmakar, 2020 ) India 84 patients with OCD Outpatient clinical sample Age range not stated Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) April-May 2020 12 % of patients had a >5% worsening of OCD severity on the Y-BOCS. ( Kaveladze et al, 2021 ) United States 196 patients with OCD Outpatient sample, patient recruited from 3 anonymous OCD online peer support communities Age range not stated, (mean age 24.8 years) Questions adapted from Dimensional Obsessive-Compulsive Scale (DOCS) June-August 2020 92.9 % of responders reported a worsening of OCD symptoms during the pandemic. Some participants were self- diagnosed with OCD ( Tundo et al, 2021 ) Italy 29 patients with OCD Outpatient clinical sample Adults, ≥18 years Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) March-June 2020 13.8 % of OCD patients reported worsening symptoms, higher than the other psychiatric illnesses included in the study.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… ( Benatti et al, 2020 ) Italy 123 patients with OCD Outpatient clinical sample, recruited from 3 tertiary clinics Age range not stated Not stated Not stated 35.8 % of patients reported worsening of symptoms during the pandemic, which was associated with developed of new obsessions and compulsions ( Chakraborty and Karmakar, 2020 ) India 84 patients with OCD Outpatient clinical sample Age range not stated Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) April-May 2020 12 % of patients had a >5% worsening of OCD severity on the Y-BOCS. ( Kaveladze et al, 2021 ) United States 196 patients with OCD Outpatient sample, patient recruited from 3 anonymous OCD online peer support communities Age range not stated, (mean age 24.8 years) Questions adapted from Dimensional Obsessive-Compulsive Scale (DOCS) June-August 2020 92.9 % of responders reported a worsening of OCD symptoms during the pandemic. Some participants were self- diagnosed with OCD ( Tundo et al, 2021 ) Italy 29 patients with OCD Outpatient clinical sample Adults, ≥18 years Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) March-June 2020 13.8 % of OCD patients reported worsening symptoms, higher than the other psychiatric illnesses included in the study.…”
Section: Search Resultsmentioning
confidence: 99%
“…Approximately 20 % of each group experienced a relapse of symptoms between initial and follow-up assessment, and this rate did not differ significantly between the groups. Similarly, linear mixed modelling did not find evidence that the pandemic had differentially impacted symptom severity trajectories versus the reference group ( Kaveladze et al, 2021 ).…”
Section: Narrative Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Experienced exposure and response prevention clinicians provided an estimate near the middle of this range, reporting that approximately 38% on average worsened during the pandemic (n = 137 clinicians) [19]. Rates of worsening were higher in the online samples, including 36% (n = 47) [20], 73% (n = 37) [18], 76% (n = 394) [21•], 76% (n = 252) [22], 93% (n = 196) [23], resulting in a pooled estimate of 77% (95% CIs 75-80%).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Although all domains significantly worsened, effect sizes appeared largest for contamination and comparisons of whether increases were greater for the contamination group were not conducted. A retrospective evaluation (n = 196) found higher worsening in those with contamination compared with symmetry symptoms (though no differences with harm or unacceptable thoughts were noted) [23]. A study of patients with remitted or partially remitted OCD found that all patients with worsened OCD during the pandemic (based on repeated Y-BOCS administrations) had a primary contamination presentation [6].…”
Section: Clinical Studiesmentioning
confidence: 99%